Hubungan Religiusitas dengan Kesehatan Mental pada Perempuan Hindu - Ni Luh Drajati Ekaningtyas (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
The number of cases of mental health disorders in Indonesia has increased every year, and dominated by women. This phenomenon needs more attention from various parties, including related aspects that can affect a person’s mental health condition, such as religiosity. This study aims to analyze the relationship between religiosity and mental health in early adult women who have early childhood. This research is a descriptive quantitative research. Data was collected using two questionnaires. The mental health questionnaire is a modification of the Mental Health Inventory (MHI-38) while the religiosity questionnaire was developed based on the theory and dimensions of religiosity from Glock and Stark. The subjects in this study were 49 early adult women who have early childhood. Data analysis was carried out by testing assumptions and hypotheses. Testing the validity of data was carried out by testing validity and reliability. The results concluded that there was a significant and positive relationship between religiosity and mental health. When a woman in her early adulthood and having early childhood has a good level of religiosity, she will have good mental health as well, and vice versa. This illustrates that individual efforts in maintaining religiosity can help maintain their mental health.